1986
DOI: 10.1021/ic00237a009
|View full text |Cite
|
Sign up to set email alerts
|

Structure-NMR correlations in halo(ligand)bis(dioximato)cobalt(III) complexes

Abstract: only an average structure was reported."The mechanism of a continuous spin transition in a solid state and the factors that determine electron-transfer rates are not yet understood although it is pointed out that a coupling between the electronic state and the vibrational modes of a molecule is important for spin transition in solution.*l In the system studied here, no evidence of first-order transition could be found. It may be important to image a intramolecular mechanism for rapid spin interconversion.Regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(23 citation statements)
references
References 5 publications
3
20
0
Order By: Relevance
“…Z The equatorial Co±N or Cu±N distances in the octahedral or square-planar parts of the trinuclear complexes (8,9) are in accord with the known vicinal dioxime complexes (r Co±N = 1.86±1.94 A Ê , r Cu±N = 1.91± 1.96 A Ê ) [29]. The values concerning interatomic angles for N±Co±N in the trinuclear complex (8) (N±Co±N = 85.47±94.34°) are also comparable to the average N±Co±N angles found in other dioxime complexes (N±Co±N = 83.63±96.43°) [24]. The Pd±S and Pd±N bond distances were longer than values given in the literature [30].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Z The equatorial Co±N or Cu±N distances in the octahedral or square-planar parts of the trinuclear complexes (8,9) are in accord with the known vicinal dioxime complexes (r Co±N = 1.86±1.94 A Ê , r Cu±N = 1.91± 1.96 A Ê ) [29]. The values concerning interatomic angles for N±Co±N in the trinuclear complex (8) (N±Co±N = 85.47±94.34°) are also comparable to the average N±Co±N angles found in other dioxime complexes (N±Co±N = 83.63±96.43°) [24]. The Pd±S and Pd±N bond distances were longer than values given in the literature [30].…”
Section: Resultssupporting
confidence: 80%
“…The 13 C-NMR spectrum of 7 revealed that, upon replacement of the hydrogen bridges by BF 2 groups, shifts of C=N and C±N carbon atoms up to 0.35±0.52 ppm occured. In the IR spectrum of this complex (7), a downward shift to for the C=N frequencies indicated coordination through the N atoms [24]. In contrast to this downward shift, this BF 2 + -bridged complex exhibited an upward shift to about a 1653 cm ±1 .…”
Section: Resultsmentioning
confidence: 89%
“…The six-coordinate mononuclear Co(III) complex [Co(HL) 2 pyCl] was synthesized as previously reported [23]. The fast atom bombardment mass spectrum of this complex exhibits a molecular ion peak at m/z ¼ 1253 [Mþ1] þ , which supports the proposed structure [24]. In the 1 H-NMR spectrum of the mononuclear Co(III) complex and the resonance of the intramolecular binding O-HÁ Á ÁO protons appear as a singlet at ¼ 16.80 ppm and this shift could easily be identified by deuterium exchange.…”
Section: Resultssupporting
confidence: 58%
“…It is known that protonation of the heterocyclic bases as well as their coordination to metal ions having a labile coordination sphere lead to deshielding of the amine protons [16]. However, the presence of the cobaloxime ring-current has an opposite effect [14,17]. The magnitude of this induced shift (ca.…”
Section: 43smentioning
confidence: 99%